Penilaian Status Kesuburan dan Pengelolaan Tanah Sawah Tadah Hujan di Desa Umbu Pabal Selatan, Kecamatan Umbu Ratu Nggay Barat - Peku Jawang, Uska (Jurnal Ilmu Pertanian Indonesia, 2021)
The rain-fed rice fields in Umbu Pabal Selatan Village are agricultural land that is always cultivated every year to meet the food needs of the villagers. Soil fertility is a piece of important information in managing rice fields to increase rice production. This study aims to evaluate the status of soil properties, soil fertility, and the direction of management of rain-sized rice fields in the village. The method used was descriptive exploration surveys with soil samples taken deliberately. Laboratory test results showed that soil pH is classified as acidic, N-total is medium, P-available is low, K-available is very high, cation exchange capacity is high, and C-organic is high. Fertility status is low (96.9 ha), moderate (194.6 ha), and high (160.3 ha). Management direction in improving fertility and nutrient deficiency is by fertilizing and water-logging. Keywords: rain-fed rice field, soil fertility, South Umbu Pabal Village